Optimizing Raw Material Mixing Equipment: A Case Study of Yili Company’s Operation in Indonesia - Xufeng, Zhang; Waworuntu, Stephanus Remond (Journal of The Community Development in Asia, 2026)
This study examines the optimization of the raw material mixing device in the production of Yili Company in Indonesia. The production process is characterized by low production and high energy consumption. Other mixing performance factors are less perfect, for instance, the consumption of energy. The potential contribution lies in proposing new equipment designs and a local mixing method that minimizes mixing energy while considering the quality of the mixture as a key parameter. This research employs a qualitative case study method to conduct an in-depth examination of Yili Indonesia Company. The research data is derived from archival research, including the company's sustainability report, internal project reports, and an analysis of related patents and technical literature. The liquid raw material mixing process in Yili Indonesia has improved the mixing efficiency, homogeneity, flexibility to the local environment, and intelligent control problems. After the process is optimized, Yili Indonesia can experience better plant performance, energy savings, and high product quality on both operational and consumer sides. The findings can lead dairy process operators to implement greener processes.